School of Economics and Finance Working Paper Series - Petchey, Jeffrey (School of Economics and Finance, Curtin Business School, 2008)
This paper shows that regional economies, such as federations or unitary countries with sub national governments, may need a system of optimal inter regional transfers to correct for various types of externalities related to factor mobility and location decisions. It is then argued that equalization schemes which take account of the differing expenditure and revenue needs of regions, create a pattern of inter regional transfers of income, but that they are inconsistent with what is required for spatial efficiency. Therefore, equalisation is incompatible with the efficient spatial allocation of mobile factors of production. It is also shown that regions have an incentive to act strategically over equalization and distort their provision of local public goods.